Baclofen and sleep apnoea syndrome: analysis of VigiBase, the WHO pharmacovigilance database. Issue 1 (11th January 2018) - Revol, Bruno; Jullian-Desayes, Ingrid; Bailly, Sébastien; Mallaret, Michel; Tamisier, Renaud; Agier, Marie-Sara; Lador, Frédéric; Joyeux-Faure, Marie; Pépin, Jean-Louis
Baclofen is a centrally acting gamma aminobutyric acid (GABA)-B agonist, widely used for chronic spasticity in neurological disorders, available in oral and intrathecal formulations. Depending on the severity of spasticity and tolerance, standard treatment includes daily oral administration of 40–80 mg [1]. The main adverse effects reported with baclofen are sedation, sleepiness, weakness, dizziness and psychological disturbances [2]. According to the depressant effects of GABA on the central nervous system, baclofen might also induce or aggravate sleep-disordered breathing by depressing central ventilatory drive and/or increasing upper airway obstruction. A single oral low dose of baclofen did not significantly impair the apnoea–hypopnoea index (AHI) in a population with moderate obstructive sleep apnoea [3], but bolus intrathecal administration of the drug increased central sleep apnoea (CSA) in patients with severe spasticity [4]. Baclofen is associated with sleep apnoea syndrome especially the high oral doses prescribed for alcohol addiction http://ow.ly/J5H730h4znW